PENGARUH PEMANTAUAN, PENAKSIRAN RISIKO DAN AKTIVITAS PENGENDALIAN TERHADAP PERILAKU ETIS KARYAWAN DALAM SISTEM PENGGAJIANA PADA PT BALI INSAN PERKASA - Ni Made Intan Sari; Tiara Kusuma Dewi; Ni Made Ernila Junpisa (Universitas Triatma Mulya, 2020)
behavior in the payroll system, (2) the effect of risk assessment on employee ethical behavior in the payroll system, (3) the effect of control activities on employee ethical behavior in the payroll system and (4) influence Simultaneous monitoring, risk assessment and control activities for employee ethical behavior in the payroll system. This research was conducted at PT Bali Insan Perkasa with a total sample of 45 people. The sampling technique uses nonprobability sampling techniques. The type of research used in this study is quantitative data while the data source is primary data. The method of data collection is done using a questionnaire. The data analysis technique uses multiple linear regression analysis with the help of SPSS Version 21.00. The results of this study indicate that (1) monitoring does not affect the ethical behavior of employees in the payroll system, (2) risk assessment does not affect the ethical behavior of employees in the payroll system, (3) control activities affect the ethical behavior of employees in the payroll system and (4 ) monitoring, risk assessment and control activities simultaneously influence the ethical behavior of employees in the payroll system.